2017
DOI: 10.1177/1759313117694629
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of tidal energy potential in India and a decision-making tool for tidal energy technology selection

Abstract: Oceans have significant renewable energy options to provide environmental friendly and clean energy. Technology for ocean energy systems and the feasibility for extraction of the same is an important area on which research is being focused worldwide. This article covers a detailed review of available tidal energy conversion technologies and case studies, with specific focus on tidal power potential in India. The proven option for tidal energy conversion is barraging. Recently, open-type turbine (usually known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The process requires high investment and efficient technology. KTs, most appropriate for the Agulhas Current, are proposed and trailed in Japan and Taiwan (Murali and Sundar, 2017).…”
Section: Ocean Thermal Energymentioning
confidence: 99%
“…The process requires high investment and efficient technology. KTs, most appropriate for the Agulhas Current, are proposed and trailed in Japan and Taiwan (Murali and Sundar, 2017).…”
Section: Ocean Thermal Energymentioning
confidence: 99%
“…Most of the extractable potential of 41000 MW in wave energy exists on the western coastline of India along Maharashtra, Goa, Karnataka, Kerala, Kanyakumari and Southern tip. A systematic approach for identification of suitable site and technology for potential site for tidal energy conversion has been proposed in [20]. The total estimated power that could be harvested in the regions identified is about 11,555 MW, with the lowest capacity factor.…”
Section: Ocean Energymentioning
confidence: 99%
“…30 crore to Rs. 60 crore per MW), Lack of experience, unpredictable environmental conditions and difficulty to assess environmental impacts are the major barriers in harnessing ocean energy [20]. Despite the inclusive policy and regulatory frameworks for the aspired quantum leap, the inadequacies in institutional mechanisms are hampering the progression of policy implementation.…”
Section: Ocean Energymentioning
confidence: 99%
“…Murali et al reported the feasibility and potential of tidal power plants in India in their research work. 20 Nazir also reported that a hybrid solar-hydro coastal power plant is technically feasible as well as commercially viable in supplying electricity in coastal areas. 21 Again, Chowdhury et al discussed the ongoing trends, ecological impacts, and technological prospects of tidal energy penetration.…”
Section: Introductionmentioning
confidence: 99%
“…However, observation on the existing literature reveals that most of the reliability studies have considered solar and/or wind, and the least focus has been given on examining the benefits from grid integration of other RESs like tidal energy, biomass, etc. Murali et al reported the feasibility and potential of tidal power plants in India in their research work 20 . Nazir also reported that a hybrid solar‐hydro coastal power plant is technically feasible as well as commercially viable in supplying electricity in coastal areas 21 .…”
Section: Introductionmentioning
confidence: 99%